The Impact of Underground Economy on the Sustainability of Tax Policy in Turkey - İsmail Kaban; Mustafa Gül (Istanbul Business Research (IBR), 2019)
This paper attempts to first evaluate the effects of underground economy on the sustainability of tax receipts, and then to search new approaches in tax policy. Underground economy reduces predictability in economic policy, decreases tax receipts, and encourages illegal activities. In Turkey, shifting taxation on indirect and labor-income taxes has created tax corridors (or tax traps), which makes the sustainability of tax receipts even more difficult. As a result, as put forward in this paper, underground economy in developed countries is lower than in developing countries. National trust in indirect taxes, which decrease the underground economy, is no longer accepted, and tax audiences in Turkey provide additional tax receipts for budgets. In Turkey, receipts from taxes on consumption have recently reached an upper limit, and this has created tax corridors, and thus tax policies have lost their elasticity. To maintain fiscal discipline, productivity of public expenditures should be increased, and the problems associated with underground economy should be tackled.
Keywords: C89; G21; M42; 650; İç denetim; Hile denetimi; Sürekli denetim; Bankacılık